Upregulation of chemokine expression in murine cornea due to mechanical trauma or endotoxin. Issue 2 (9th November 2007) - Pillai, R G; Beutelspacher, S C; Larkin, D F P; George, A J T
Abstract : Background and aims: Allograft rejection is the commonest cause of corneal transplant failure and is significantly higher in high-risk patients. Corneal tissue is reported to produce chemokines in response to stress/inflammation. Expression of chemokines is central to the recruitment of leucocytes during inflammatory events. This study was designed to evaluate the effects of surgical trauma or storage conditions on chemokine expression. Methods: Murine corneas were manipulated by incubation in different conditions for up to 24 h, by the addition of endotoxin or by surgical trauma. The ex vivo production of chemokines was assessed using a real-time reverse-transcriptase PCR (RT-PCR) assay to measure mRNA encoding MIP-1α, MIP-1β and MIP-1γ, MCP1, IP-10, lymphotactin, fractalkine, RANTES, eotaxin, MIG, MIP2 and the cytokine MIF. The expression of RANTES was also determined by ELISA, and the ability of supernatant from corneas on chemotaxis of cells was also determined. Finally, we compared the survival of corneal grafts that had (or had not) been treated with endotoxin. Results: We found that on incubation in corneal storage medium, expression of mRNA for the majority of these chemokines greatly increased. Upregulation of chemokine mRNA expression was also seen following the mechanical trauma of suture insertion and exposure of the cornea to endotoxin. In the case of mechanical trauma, functional activity of the chemokines was demonstrated using a chemotaxis assay. Orthotopic transplantation of LPS-treated corneas, in which chemokine expression was elevated, resulted in increased infiltration by leucocytes and more rapid rejection of allogeneic grafts. Conclusion: Our results indicate that ex vivo storage and manipulation of murine corneas can influence the expression of chemokines in corneas, and can result in earlier graft rejection. This may be of importance when considering procedures for manipulation and ex vivo storage of donor corneas prior to transplantation, as well as the surgical procedure itself.